1980
DOI: 10.1038/clpt.1980.9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nadolol β-blockade on blood pressure in hypertension

Abstract: Nadolol, a nonselective beta adrenoceptor antagonist, was evaluated in 9 normal sybjects with essential hypertension for ability to inhibit exercise-induced changes in double-product (systolic pressure x heart rate). Propranolol and placebo were included as positive and negative controls. The beta antagonists were administered orally in single doses at 10, 20, 40, and 80 mg on a crossover basis. Both nadolol and propranolol induced comparable dose-related inhibition of double-product. Duration of beta receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…We have been unable to relate steady state drug levels to clinical response or reduction in serum T3 nor were Murchison et al (1979), although a significant correlation between steady state propranolol levels, weight change, reduction in therapeutic index and reduction in serum T3 has been shown (Feely et al, 1980). In hypertensive patients serum nadolol concentration was related to change in double product and to reduction in blood pressure (Duchin et al, 1980). The present study has shown a modest but significant fall in serum T3 (7%) and a rise in rT3 levels (13%) while the serum T4 was unchanged.…”
Section: Discussionmentioning
confidence: 80%
“…We have been unable to relate steady state drug levels to clinical response or reduction in serum T3 nor were Murchison et al (1979), although a significant correlation between steady state propranolol levels, weight change, reduction in therapeutic index and reduction in serum T3 has been shown (Feely et al, 1980). In hypertensive patients serum nadolol concentration was related to change in double product and to reduction in blood pressure (Duchin et al, 1980). The present study has shown a modest but significant fall in serum T3 (7%) and a rise in rT3 levels (13%) while the serum T4 was unchanged.…”
Section: Discussionmentioning
confidence: 80%
“…Although we did not find significant differences in the AUEC 0–8 for PR, SBP and DBP between groups partly due to the small sample size, those pharmacodynamic responses to nadolol tended to decline with concomitant ingestion of brewed green tea. It has been reported that nadolol exerts dose‐related decreases of heart rate and SBP as indexed by double product, which is calculated by heart rate × SBP, 16 and therefore it is assumed that the decrease in plasma concentration of nadolol could result in the reduction of its β‐blocking effect. However, it should be noted that we only recorded the acute response to nadolol after single oral administration.…”
Section: Resultsmentioning
confidence: 99%
“…The investigator's estimation of the clinical response of the patients both on nadolol alone and on nadolol plus diuretic at stabilisation of blood pressure is shown in Table V. 3,864 (91.45%) of patients on nadolol alone were rated excellent or good, as were 2,090 (90.80%) patients on nadolol plus diuretic.…”
Section: Dosage and Treatmentmentioning
confidence: 99%
“…Following oral administration, peak serum levels are attained in 2‐4 hours, absorption not being affected by food. Maximal beta‐receptor inhibition occurring 5‐8 hours after the first dose 3 . Steady state serum levels occur after 6‐9 days 4 , accumulation has not been shown 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation